2020
DOI: 10.1128/mra.00820-20
|View full text |Cite
|
Sign up to set email alerts
|

16S rRNA Gene Diversity in Ancient Gray and Pink Salt from San Simón Salt Mines in Tarija, Bolivia

Abstract: DNA from 250 million-year-old pink and gray salts from mines in Tarija, Bolivia, subjected to 16S rRNA gene amplicon sequencing and analysis provided evidence for similar but distinct prokaryotic communities. The results constitute a snapshot of archaeal and bacterial microorganisms in these remote and ancient salt deposits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…In congruence with this speculation, 16S rRNA genes of Anaeromyxobacteraceae , which have rather moderate GC contents (57.6%–58.6%, Fig. S3) compared to that of their nif genes, have been constantly detected by PCR amplicon surveys (Mitter et al, 2021; Pecher et al, 2020; Sun et al, 2018). However, note that GC richness may not solely explain why Anaeromyxobacteraceae have been overlooked as diazotrophs in amplicon surveys, since there are examples of high GC content (63.4%–68.0%) nitrogenase genes belonging to Frankia species (phylum Actinobacteria ) that are successfully amplified by PCR-based methods (Collavino et al, 2014; Dahal et al, 2017).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…In congruence with this speculation, 16S rRNA genes of Anaeromyxobacteraceae , which have rather moderate GC contents (57.6%–58.6%, Fig. S3) compared to that of their nif genes, have been constantly detected by PCR amplicon surveys (Mitter et al, 2021; Pecher et al, 2020; Sun et al, 2018). However, note that GC richness may not solely explain why Anaeromyxobacteraceae have been overlooked as diazotrophs in amplicon surveys, since there are examples of high GC content (63.4%–68.0%) nitrogenase genes belonging to Frankia species (phylum Actinobacteria ) that are successfully amplified by PCR-based methods (Collavino et al, 2014; Dahal et al, 2017).…”
Section: Resultssupporting
confidence: 59%
“…In contrast, our shotgun metagenomic and metatranscriptomic analyses of paddy soil in Japan have detected highly abundant nif genes and transcripts from the families Anaeromyxobacteraceae and Geobacteraceae within Deltaproteobacteria (also classified as the phyla Myxococcota and Desulfobacterota , respectively) compared to the findings for the conventional diazotrophic groups (Masuda et al, 2017). Considering their prevalence across many soil types as revealed by 16S rRNA gene-based surveys (Mitter et al, 2021; Pecher et al, 2020; Sun et al, 2018), members of the families Anaeromyxobacteraceae and Geobacteraceae may thus represent universal and/or major drivers of terrestrial nitrogen fixation. However, these clades, which are well-known iron-reducing bacterial groups (Weber et al, 2006), have received considerably less attention as diazotrophs in soil than the conventional groups because of the less frequent detection of their nif genes in soil environments in previous PCR amplicon surveys.…”
Section: Introductionmentioning
confidence: 99%
“…Several amplicon-based studies have also reported the occurrence of Geobacteraceae nitrogenase genes in soils [15][16][17][18]. Considering their prevalence across many soil types as revealed by 16S rRNA gene-based surveys [19][20][21], members of the families Anaeromyxobacteraceae and Geobacteraceae may thus represent universal and/or major components of diazotrophic microbiome in various terrestrial environments. However, these clades, which are well-known iron-reducing bacterial groups [22], have received considerably less attention as diazotrophs in soil than the conventional groups.…”
Section: Introductionmentioning
confidence: 99%
“…H alophilic microbes capable of surviving extreme conditions are of interest for biotechnology and astrobiology (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Our recent focus has been on high elevation and subsurface hypersaline environments which yield polyextremophilic varieties.…”
mentioning
confidence: 99%